Towards digital engineering: the advent of digital systems engineering. (7th September 2020) - Huang, Jingwei; Gheorghe, Adrian; Handley, Holly; Pazos, Pilar; Pinto, Ariel; Kovacic, Samuel; Collins, Andrew; Keating, Charles; Sousa-Poza, Andres; Rabadi, Ghaith; Unal, Resit; Cotter, Teddy; et al.
Digital engineering, the digital transformation of engineering to leverage digital technologies, is coming globally. This paper explores digital systems engineering, which aims at developing theory, methods, models, and tools to support digital engineering practice. A critical task is to digitalise engineering artefacts, thus enabling information and model sharing, traceability, and accountability across platforms, across lifecycle, and across domains. We identify challenges and enabling digital technologies; analyse the transition from traditional engineering to digital engineering; define core concepts, including digitalisation, unique identification, digitalised artefacts, digital augmentation, and others; present a big picture of digital systems engineering in four levels: vision, strategy, action, and foundation; briefly discuss each of main areas of research. Digitalisation enables fast infusing and leveraging novel digital technologies; unique identification enables information traceability and accountability in lifecycle; provenance enables tracing dependency relations among engineering artefacts, supporting model reproducibility and replicability, and helping with trustworthiness evaluation of digital artefacts.